On the selective aerobic oxidation of benzyl alcohol with Pd/Au-nanoparticles in batch and flow - Alex, Hannes; Steinfeldt, Norbert; Jähnisch, Klaus; Bauer, Matthias; Hübner, Sandra (Nanotechnology Reviews)
Abstract Nanoparticles (NP) have specific catalytic properties, which are influenced by parameters like their size, shape, or composition. Bimetallic NPs, composed of two metal elements can show an improved catalytic activity compared to the monometallic NPs. We, herein, report on the selective aerobic oxidation of benzyl alcohol catalyzed by unsupported Pd/Au and Pd NPs at atmospheric pressure. NPs of varying compositions were synthesized and characterized by UV/Vis spectroscopy, transmission electron microscopy (TEM), and small-angle X-ray scattering (SAXS). The NPs were tested in the model reaction regarding their catalytic activity, stability, and recyclability in batch and continuous procedure. Additionally, in situ extended X-ray absorption fine structure (EXAFS) measurements were performed in order to get insight in the process during NP catalysis.
Keywords: Surfaces; Coatings and Films; Process Chemistry and Technology; Energy Engineering and Power Technology; Biomaterials; Medicine (miscellaneous); Biotechnology

Studienprogramme als didaktische Gestaltungs-und Untersuchungseinheit: Theoretische Grundlegung und empirische Analyse - Jenert, Tobias
Mit welchen Erwartungen und Anforderungen sehen sich Studierende im Hochschulalltag konfrontiert? Wie muss nach Ansicht der Studierenden gehandelt werden, um das Studium "erfolgreich" zu bewältigen? Wie laufen die Auswahl unterschiedlicher Lernaktivitäten im Studium sowie die Allokation von Ressourcen im Detail ab? Diese und weitere Fragen sind vor allem im Zusammenhang mit der Debatte um die Bologna-Reform stärker in den Mittelpunkt gerückt. Denn während modularisierte Curricula und Credit-Point-Systeme oft nach administrativ-organisatorischen Gesichtspunkten eingeführt wurden, hat die Gestaltung der Studienstrukturen auf Programmebene zwangsweise Auswirkungen auf das Studienhandeln - und damit auch auf das Lernen der Studierenden. Es gibt viele Vermutungen über die "Wirkungen" von Bologna auf das Studieren: Die Rede ist von Verschulung, Entwissenschaftlichung und Arbeitsüberlastung und Studierende stehen im Verdacht, ihren Studienpfad eher im Sinne einer Credit-Point-Jagd denn interessengeleitet zu gestalten. In der Regel bleibt es dabei jedoch bei anekdotischen Beobachtungen - es fehlt bislang an gesicherten Erkenntnissen über Zusammenhänge zwischen Bologna-konformen Studienkontexten und dem Handeln Studierender. Denn obschon Studierende seit langem Gegenstand der Forschung sind, ist bislang wenig darüber bekannt, wie sie den langfristigen Bildungsprozess eines ganzen Studiums gestalten. Stattdessen wurde vorwiegend das Lernen im engeren Sinne, das so genannte "Classroom Learning" untersucht. Diejenigen, die Studienprogramme nach didaktischen Gesichtspunkten gestalten wollen müssen wissen, wie Studierende mit unterschiedlichen Studienstrukturen umgehen. Denn nur so ist eine planvolle Programmgestaltung im Sinne pädagogischer Zielsetzungen und didaktischer Prinzipien möglich. Die vorliegende Arbeit nimmt diese Problemstellung auf und untersucht, welche Zielvorstellungen und Handlungsstrategien Studierende bei der Bewältigung ihres Studienalltags in unterschiedlichen Bologna-konformen Studienprogrammen entwickeln. Im Einzelnen wird gefragt, (1) welche Vorstellungen, Wahrnehmungen und Handlungslogiken das Handeln Studierender in unterschiedlichen Studienprogrammen prägen und (2) welche programmspezifischen Kontextbedingungen die Herausbildung dieser handlungsleitenden Charakteristika beeinflussen. Ausgehend von diesen beiden Fragestellungen wird zunächst ein theoretisch fundierter Analyserahmen für Studienprogramme entwickelt. Darauf aufbauend werden verschiedene Studienprogramme empirisch untersucht, um schliesslich Design-Prinzipien für die Gestaltung von Studienprogrammen zu formulieren. Es wird nicht davon ausgegangen, dass Studienstrukturen das Handeln Studierender im Sinne eines kausalen Wirkungszusammenhangs bestimmen. Vielmehr wird gefragt, was die Studierenden mit den Strukturen, auf die sie treffen, machen. Studienprogramme werden als kulturelle Einheiten verstanden, innerhalb derer sich spezifische handlungsleitende Vorstellungen und Normen entwickeln. Diese impliziten Regeln des Studienhandelns - das so genannte "Hidden Curriculum" - und vor allem auch die dahinterliegenden Konstruktionsprozesse aufzudecken, ist Ziel dieser Arbeit.
Keywords: Studierverhalten; Hochschuldidaktik; Lernpsychologie; Kulturpsychologie; Bologna-Prozess; Curriculumentwicklung; Hochschulbildung; Study programme; Bologna-process; educational development; cultural psychology; higher education; curriculum development

Beyond process monitoring: A proof-of-concept of event-driven business activity management - Janiesch, Christian; Matzner, Martin; Müller, Oliver (Business Process Management Journal)
Purpose – The purpose of this paper is to show how to employ complex event processing (CEP) for the observation and management of business processes. It proposes a conceptual architecture of BPM event producer, processor, and consumer and describes technical implications for the application with standard software in a perfect order scenario. Design/methodology/approach – The authors discuss business process analytics as the technological background. The capabilities of CEP in a BPM context are outlined an architecture design is proposed. A sophisticated proof-of-concept demonstrates its applicability. Findings – The results overcome the separation and data latency issues of process controlling, monitoring, and simulation. Distinct analyses of past, present, and future blur into a holistic real-time approach. The authors highlight the necessity for configurable event producer in BPM engines, process event support in CEP engines, a common process event format, connectors to visualizers, notifiers and return channels to the BPM engine. Research limitations/implications – Further research will thoroughly evaluate the approach in a variety of business settings. New concepts and standards for the architecture's building blocks will be needed to improve maintainability and operability. Practical implications – Managers learn how CEP can yield insights into business processes' operations. The paper illustrates a path to overcome inflexibility, latency, and missing feedback mechanisms of current process modeling and control solutions. Software vendors might be interested in the conceptualization and the described needs for further development. Originality/value – So far, there is no commercial CEP-based BPM solution which facilitates a round trip from insight to action as outlines. As major software vendors have begun developing solutions (BPM/BPA solutions), this paper will stimulate a debate between research and practice on suitable design and technology.
Keywords: Architecture; Business activity monitoring; Business process management; Business process re-engineering; Complex event processing; Computer software; Standard software

Non-perturbing cavitation detection / monitoring in sonochemical reactors - Bornmann, Peter; Hemsel, Tobias; Sextro, Walter; Maeda, Takafumi; Morita, Takeshi (Ultrasonics Symposium (IUS), 2012 IEEE International)
To optimize the ultrasound irradiation for cavitation based ultrasound applications like sonochemistry or ultrasound cleaning, the correlation between cavitation intensity and the resulting effect on the process is of interest. Furthermore, changing conditions like temperature and pressure result in varying acoustic properties of the liquid. That might necessitate an adaption of the ultrasound irradiation. To detect such changes during operation, process monitoring is desired. Labor intensive processes, that might be carried out for several hours, also require process monitoring to increase their reliability by detection of changes or malfunctions during operation. In some applications cavitation detection and monitoring can be achieved by the application of sensors in the sound field. Though the application of sensors is possible, this necessitates modifications on the system and the sensor might disturb the sound field. In other applications harsh, process conditions prohibit the application of sensors in the sound field. Therefore alternative techniques for cavitation detection and monitoring are desired. The applicability of an external microphone and a self-sensing ultrasound transducer for cavitation detection were experimentally investigated. Both methods were found to be suitable and easily applicable.
Keywords: cavitation; chemical reactors; microphones; process monitoring; reliability; ultrasonic applications; ultrasonic waves; acoustic properties; cavitation based ultrasound applications; cavitation intensity; change detection reliability; external microphone; malfunction detection reliability; nonperturbing cavitation detection; nonperturbing cavitation monitoring; process monitoring; self-sensing ultrasound transducer; sonochemical reactors; sonochemistry; ultrasound cleaning; ultrasound irradiation; Acoustics; Liquids; Monitoring; Sensors; Sonar equipment; Transducers; Ultrasonic imaging

Die Studierenden? - Ein sozio-kultureller Blick auf das Studieren in Bologna-Strukturen - Jenert, Tobias (Zeitschrift für Hochschulentwicklung)
Die hochschulbezogene Lernforschung konzentierte sich bislang vor allem auf das Lernen Studierender im Vorlesungssaal (Classroom Learning). Im Zuge der Bologna-Diskussion stellt sich jedoch vermehrt die Frage, wie Studierende den langfristigen Bildungspfad eines ganzen Studiums gestalten. Denn obschon Studierende seit langem Gegenstand der Forschung sind, ist bislang wenig dazu bekannt, wie Lernaktivitäten ausgewählt und Ressourcen im Studium verteilt werden. Der Beitrag nimmt diese Frage auf und untersucht, welche Handlungsstrategien Studierende bei der Bewältigung ihres Studienalltags in unterschiedlichen Bologna-konformen Studienprogrammen entwickeln und welche Rahmenbedingungen dabei eine Rolle spielen.
Keywords: Programmentwicklung; Bologna; Studierende; Kulturpsychologie; Studienprogramm

A blueprint for event-driven business activity management - Janiesch, Christian; Matzner, Martin; Müller, Oliver (Lecture Notes in Computer Science)
Keywords: Reference architecture; business activity management; business process analytics; business process management; complex event processing

Simulating Tightly Intermeshing, Co-Rotating Twin Screw Extruders with SIGMA - Kretzschmar, Nils; Schöppner, Volker (Proceedings of the 2010 Summer Computer Simulation Conference)
A large proportion of plastics today is compounded, which means the process from refining a raw material to the processable material. For this process compounding extruders are used which mostly involve tightly intermeshing, co-rotating twin screw extruders. These extruders consist of two closely spaced screws which rotate in the same direction and convey the raw material to the screw tip. These screws are surrounded by several barrel modules which heat or cool the material. As the whole design of the machine is modularly arranged the process behavior of a twin screw extruder depends for the main part on the arrangement of the screw and the barrel elements. Until today this arrangement and process optimization is conducted by experienced engineers and with the help of trial-and-error methods. Furthermore, theoretical models are used with which the behavior of the extruder is estimated. As these models are mostly very complex they are only made available with the realization in different software projects. One of the tools is called SIGMA. Within this paper SIGMA is introduced as a software to optimize a twin screw extruder. SIGMA supports the engineer already in the early stages of the extruder arrangement.
Keywords: process optimization; polymer engineering; compounding; twin screw extruder; simulation

RTOS-Aware Refinement for TLM2.0-based HW/SW Design - Becker, Markus; Di Guglielmo, Giuseppe; Fummi, Franco; Müller, Wolfgang; Pravadelli, Graziano; Xie, Tao (Proceedings of DATE’10)
Refinement of untimed TLM models into a timed HW/SW platform is a step by step design process which is a trade-off between timing accuracy of the used models and correct estimation of the final timing performance. The use of an RTOS on the target platform is mandatory in the case real-time properties must be guaranteed. Thus, the question is when the RTOS must be introduced in this step by step refinement process. This paper proposes a four-level RTOS-aware refinement methodology that, starting from an untimed TLM SystemC description of the whole system, progressively introduce HW/SW partitioning, timing, device driver and RTOS functionalities, till to obtain an accurate model of the final platform, where SW tasks run upon an RTOS hosted by QEMU and HW components are modeled by cycle accurate TLM descriptions. Each refinement level allows the designer to estimate more and more accurate timing properties, thus anticipating design decisions without being constrained to leave timing analysis to the final step of the refinement. The effectiveness of the methodology has been evaluated in the design of two complex platforms.
Keywords: Timing; Hardware; Operating systems; Process design; Accuracy; Standards development; Context modeling; Real time systems; Communication channels; Microprogramming

The SATURN Approach to SysML-based HW/SW Codesign - Müller, Wolfgang; He, Da; Mischkalla, Fabian; Wegele, Arthur; Larkham, Adrian; Whiston, Paul; Penil, Pablo; Villar, Eugenio; Mitas, Nikolaos; Kritharidis, Dimitros; Azcarate, Florent; Carballeda, Manuel (Proceedings of the IEEE Computer Society Annual Symposium on VLSI)
The main obstacle for the wide acceptance of UML and SysML in the design of electronic systems is due to a major gap in the design flow between UML-based modeling and SystemC-based verification. To overcome this gap, we present an approach developed in the SATURN project which introduces UML profiles for the co-modeling of SystemC and C with code generation support in the context of the SysML tool suite ARTiSAN Studio®. We finally discuss the evaluation of the approach by two case studies.
Keywords: Communicate Sequential Process Virtual Platform Smart Camera Synchronous Data Flow Artisan Studio

Design and modeling of a domain ontology for fire protection - Pottebaum, Jens; Japs, Anna Maria; Prödel, Stephan; Koch, Rainer (ISCRAM 2010 -- 7th International Conference on Information Systems for Crisis Response and Management)
Keywords: Command and control process; Command and control systems; Design and modeling; Domain ontologies; Emergency response; Fire extinguishers; Fire protection; Heterogeneous domains; Information analysis; Information sharing; Information systems; Interoperability; Ontology language; Semantic technologies; Semantic Web; Semantics